Family size and child outcomes: Is there really no trade-off? - Olof Åslund; Hans Grönqvist (Institute for Labour Market Policy Evaluation (IFAU), 2007)
Recent empirical work questions the negative relationship between family size and children's attainments proposed by theoretical work and supported by a large empirical literature. We use twin births as an exogenous source of variation in family size in an unusually rich dataset where it is possible to separately look at intermediate and long run outcomes. We find little evidence of a causal effect on long term outcomes such as years of schooling and earnings, and studies that do not take selection effects into account are likely to overstate the effects. We do, however, find a small but significant negative impact of family size on grades in compulsory and secondary school.
Keywords: I20; J13; 330; Family size; twin births; education; earnings; Familie; Bildungsniveau; Bildungsertrag; Schweden